Effect of isotretinoin on tooth germ and palate development in mouse embryos. - Balducci-Roslindo, Eleny [UNESP]; Silvério, Karina Gonzales [UNESP]; Jorge, Maria Augusta [UNESP]; Gonzaga, Heron Fernando de Souza [UNESP] (My University, 2001)
Vitamin A and its derivatives, retinoic acid, tretinoin and isotretinoin, are currently used in dermatological treatments. The administration of high doses of this vitamin provokes congenital malformations in mice: cleft palate, maxillary and mandibular hypoplasia and total or partial fusion of the maxillary incisors. This study compares the tooth germs of the first maxillary and mandibular molars of fetal mice submitted to isotretinoin during organogenesis. Twelve 60-day-old female Mus musculus were divided into two groups on the 7th day of pregnancy: treated group--1 mg isotretinoin per kg body weight, dissolved in vegetable oil, was administered from the 7th to the 13th day of pregnancy; control group--vegetable oil in equivalent volume was administered orally for the same period. On the 16th day of pregnancy, the females were sacrificed, the fetuses were removed and their heads amputated. After standard laboratory procedures, 6-micron thick serial slices were stained with hematoxylin and eosin for optical microscopy examination. The results showed that both groups had closed palates with no reminiscence of epithelial cells; however, the first molar germs of the isotretinoin-treated animals showed delayed development compared to the control animals.
Keywords: isotretinoin; animal; drug effect; female; molar tooth; mouse; palate; pregnancy; prenatal development; tooth flora; Animals; Embryonic and Fetal Development; Female; Isotretinoin; Mice; Molar; Palate; Pregnancy; Tooth Germ